Luke's story [large type] - LaHaye, Tim, 1926-2016 (LaHaye, Tim, 1926-2016. Jesus chronicles, 2009)
In the third book of the Jesus Chronicles, Luke, a young Greek slave, meets Saul of Tarsus. Saul is a Hebrew debater who Luke sees as a great role model. When Saul mentions a man named Jesus who performs great miracles, Luke is not sure he believes. However, when Jesus performs miracles on one of Luke's own patients, his mind is changed.